Intraoperative Use of Ultrasonography in the Reduction of Zygomatico-Maxillary Complex Fractures. Issue 3 (September 2022) - Eswari, Jagdish; Ravindran, C.; Deepak, C.
Study Design: A single blind randomized controlled study. Objective: The aim of this study is to evaluate the use of ultrasonography intraoperatively to assess the reduction of unilateral zygomatic complex fractures with a control group using the conventional blind digit palpation. Methods: The study comprised of a sample size of 24 patients with 21 male and 3 female patients. Patients of all age groups diagnosed with unilateral displaced zygomatic complex fracture with or without mandible fracture were included in the study. The subjects were randomized into study and control groups based on a standard protocol with a total of 24 patients. Imaging was in the form of a preoperative and postoperative 3D computed tomography scan with reconstruction of the maxilla and mandible to interpret the diagnosis for all subjects. The inter-fracture distance of the fractured infraorbital rim were measured in 3 dimensions (antero-posterior, medio-lateral and supero-inferior) and compared pre and postoperatively. Preoperative, intraoperative and postoperative ultrasonographic examination was performed and recorded on all patients at the frontozygomatic region, infraorbital rim and zygomatic buttress to assess the proximity of the fractured margins pre reduction, post reduction and post fixation of the fracture segments. Result: Statistical analytic results were significant in all 3 dimensions when measured postoperatively using computed tomography. Conclusion: Ultrasonography is an effective screening and intraoperative tool in the armamentarium of oral and maxillofacial surgery to assess zygomatic complex fractures, avoiding incisions in aesthetic areas of the maxillofacial region.